Case study of flood risk and vulnerability in the city of Atlanta – A social, economic, technical, and institutional perspective - Prerna Singh; Adjo Amekudzi-Kennedy; Baabak Ashuri; Ty Parrillo; Derek Rizzi; Russell Clark; Brian Woodall; Heejun Chang (Resilient Cities and Structures, 2025)
The negative impacts of natural hazards on communities at all scales have been increasing. Floods comprise one such natural hazard that has emerged as one of the most destructive in the US and worldwide. While a lot of damage is estimated in terms of the cost of rebuilding infrastructure and direct loss of economy, the negative impacts of such disruptions go beyond the physical infrastructure. The impact on (and of) the social and institutional framework is rarely examined in conjunction with the physical and technical aspects. This paper examines flood vulnerability and risk of a community at an intersection of social, ecological, technical, and intuitional perspectives, and presents a framework for a holistic flood vulnerability and risk assessment that has a strong foundation in all four aspects of a resilient community. The study builds on the existing risk, vulnerability, and hazard assessment approaches, and refines them with a holistic perspective. The study uses a mixed method approach with qualitative and quantitative methodologies to assess flood occurrence probabilities, vulnerability, and risk from the social, ecological, technical, and institutional perspectives. A case study of the City of Atlanta is conducted using the framework to assess the overall vulnerability and risk of the city. The results of this analysis show that the regions that have the highest probability of flood hazard occurrence also appear to have the highest social, ecological, and technical vulnerabilities in the Atlanta area. While the results are intuitive, the applications support a focus on holistic resilience building across these four criteria. This study is potentially useful to practitioners, researchers, government agencies, and community organizations working to mitigate flood risk particularly as this risk continues to evolve with the changing climate.